Pengaruh Keragaman Menu, Kualitas Pelayanan Dan Harga Terhadap Minat Beli Pada Hakui Coffee Tulungagung - Iwanda Sekar Wisesa; Indah Listyani; Zulfia Rahmawati (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
The world of the food and beverage industry is developing very rapidly. In Indonesia, this is characterized by the variety of culinary delights available with regional and modern flavors. "The rapid development of culinary arts in Indonesia means that entrepreneurs have to think hard to remain creative in order to be able to fight new, innovative competitors. The current phenomenon means that old entrepreneurs must have new innovations to be able to maintain their business. Because it is known that many young entrepreneurs have created food and beverage products that offer delicious flavors at economical prices. This kind of competition is difficult to avoid. This research examines menu diversity, service quality and prices at Hakui Coffee Tulungagung. These three interrelated variables seem interesting if used as research objects. The type of research used by researchers is descriptive quantitative. The analysis techniques used are validity test instruments, reliability tests, classical assumption tests, multiple regression tests, t tests, F tests, coefficient of determination tests. The results of this research show that the first hypothesis proposed states that menu diversity has a significant effect on buying interest. Partially, according to the t test of 2.986 with a significance level of 0.060 > 0.05, H1 is accepted and H0 is rejected, where the research results show that diversity The menu has a significant effect on buying interest as evidenced by the results obtained in the form of a correlation coefficient of 0.231 and a partial significance test which produces a t-count of 2.096.